(untitled) (Fiep Bulletin - online, 2014)
Basing the study on the concept of corporal image and the phenomenon of the new circus, the author proposes to investigate the motor-psychological relations of the circus activities. The historical constitution of the circus and its contemporary expression tangles the environmental application of this study. After presenting a brief design of the new circus, the author seeks out to relate the kinesthesial effects and the positive influences of these activities on the individual cognitive development based on the holistic vision of the human being.